Pre‐orogenic upper crustal softening by lower greenschist facies metamorphic reactions in granites of the central Pyrenees. (7th January 2020) - Airaghi, Laura; Bellahsen, Nicolas; Dubacq, Benoît; Chew, David; Rosenberg, Claudio; Janots, Emilie; Waldner, Maxime; Magnin, Valérie
Abstract: Pre‐kinematic greenschist facies metamorphism is often observed in granites and basement units of mountain belts, but rarely dated and accounted for in orogenic cycle reconstructions. Studying pre‐kinematic alteration is challenging because of its usual obliteration by subsequent syn‐kinematic metamorphism often occurring at conditions typical of the brittle–ductile transition. It is, however, to be expected that pre‐kinematic alteration has major implications for the rheology of the upper crust. In the 305 Ma‐old Variscan basement of the Bielsa massif (located in the Axial Zone of the Pyrenees), successive fluid–rock interaction events are recorded in granites below 350°C. Combined microstructural and petrographic analysis, low‐ T thermobarometry and in situ U–Th/Pb dating of anatase, titanite and monazite show extensive pre‐orogenic (pre‐Alpine) and pre‐kinematic alteration related to feldspar sericitization and chloritization of biotite and amphibole at temperatures of 270–350°C at 230–300 Ma. This event is followed by a second fluid–rock interaction stage marked by new crystallization of phyllosilicates at 200–280°C and is associated with the formation of mylonitic shear zones and fractures parallel to the shear planes. U–Pb anatase and monazite ages as well as the microtextural relationships of accessory minerals suggest an age for this event at 40–70 Ma, consistent with independent regional geology constraints. The Variscan basement was therefore softened at late to post‐Variscan time, at least 150–200 Ma before the main Alpine shortening while Alpine‐age compression ( c. 35–50 Ma) leads to the formation of a dense net of mylonites. The associated deformation, both distributed at the scale of the Bielsa massif and localized at decametric scale in mylonitic corridors, precedes the strain localization along the major thrusts of the Axial Zone. The Bielsa massif is a good example where inherited, pre‐orogenic upper crustal softening controls the deformation patterns in granitic basement units through low‐grade metamorphic reactions.